Threshold concept in intellectual property law. Issue 4 (11th July 2016) - Azam, Monirul
Abstract : Purpose: This paper aims to identify the threshold concept in intellectual property (IP) law. Design/methodology/approach: It used doctrinal methods for such identification based on the existing pedagogical scholarship in the field of effective teaching and learning. Findings: It explained how the use of the threshold concept in IP law education could facilitate understanding of IP law from globalised perspectives and validate use of IP in a balanced way. Research limitations/implications: It is yet to be tested for practical curriculum design in different jurisdictions. Practical implications: The understanding of threshold concepts in IP law could generate "eureka" moments, when, after a long struggle, students come to a deep understanding of a new concept. Social implications: This will facilitate social acceptance of IP for balancing global obligation and national developmental and social goals. Originality/value: Till date, little work has been undertaken on the threshold concepts on IP law. Therefore, this study tried to make a unique contribution by identifying threshold concepts in intellectual property law.